Land income and large capitalist planting of oil palm in the Brazilian Amazon - Trindade, José Raimundo; Paixão Junior, Paulo Roberto Carneiro da (Revista Economia Ensaios, 2024)
This article deals with the relationship between capitalist land rent and oil palm in the state of Pará. The objective of the research was to explain, based on the Marxist theory of land rent, why the state of Pará (with emphasis on the micro-region of Tomé-Açu) presents itself as the main producer and with the highest productive averages of Brazilian oil palm. To develop this analysis, the theory of land rent established by Marx (2017 [1894]) has been used, detailing the four modalities of land rent (monopoly rent, absolute rent, differential rent I and differential rent II), considering their theoretical and practical interactions. As an empirical procedure, secondary data on location, climate and soil conditions related to the development of the crop, as well as the size of the capital involved, were analyzed.